Role of Emerging Technologies in Improving Procurement Efficiency and Effectiveness in Ghana - Acheampong, Felix (Global Journal of Purchasing and Procurement Management, 2024)
Purpose: The aim of the study was to examine the role of emerging technologies in improving procurement efficiency and effectiveness in Ghana. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The role of emerging technologies in improving procurement efficiency and effectiveness in Ghana has been transformative, driving significant advancements in the procurement landscape. The adoption of technologies such as blockchain, artificial intelligence (AI), Internet of Things (IoT), and big data analytics has streamlined procurement processes, enhanced transparency, and fostered better decision-making. Emerging technologies have automated repetitive and time-consuming tasks, reducing manual errors and speeding up procurement cycles. AI and machine learning algorithms have enabled predictive analytics, allowing procurement professionals to forecast demand more accurately, optimize inventory levels, and negotiate better with suppliers based on data-driven insights. Unique Contribution to Theory, Practice and Policy: Technology Acceptance Model, Resource-Based View (RBV) & Transaction Cost Economics (TCE) may be used to anchor future studies on role of emerging technologies in improving procurement efficiency and effectiveness in Ghana. Organizations can benefit significantly by investing in training and development programs tailored to equip procurement professionals with the skills needed to leverage emerging technologies effectively. Hands-on workshops, certification courses, and mentorship programs focused on technology integration should be prioritized to bridge existing skill gaps and build a workforce capable of implementing and managing these advanced procurement tools. Governments and regulatory bodies play a pivotal role in creating an enabling environment for the widespread adoption of emerging technologies in procurement. Developing flexible regulatory frameworks that accommodate the unique characteristics and risks associated with these technologies, such as data privacy and cybersecurity concerns, is essential. Policymakers should also consider incentives such as tax credits, grants, and subsidies to encourage organizations to invest in technology upgrades and innovations that enhance procurement efficiency and effectiveness.